1976
DOI: 10.1159/000301391
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Mechanisms of Egg Transport in the Ampulla of the Rabbit Oviduct

Abstract: Ampullary transport of supravitally stained cumulus egg masses was studied in intact oviducts of anesthetized rabbits whose abdomens had been opened for observation. Following observations of normal transport, muscular activity of the ampulla was inhibited pharmacologically with Acepromazine®, a preanesthetic tranquilizer. With muscle contractions blocked, egg transport continued but in a dramatically altered fashion; in the final two thirds of the ampulla the motion changed from rapid to-and-fro movements to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…The reduced transport rate was not due to an inhibitory effect of the poly(L-lysine) on muscle contractility. Because inhibition of muscle contraction alone does not affect the rate of ovum transport (5,6), it may be that normally the cilia provide the primary propulsive force for ovum movement down the ampulla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced transport rate was not due to an inhibitory effect of the poly(L-lysine) on muscle contractility. Because inhibition of muscle contraction alone does not affect the rate of ovum transport (5,6), it may be that normally the cilia provide the primary propulsive force for ovum movement down the ampulla.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it has been generally accepted that the cilia of the epithelial cells that line the oviduct are responsible for movement of the cumulus over the fimbria into the ampulla and that the contractile activity of the smooth muscle cells in the wall of the ampulla is responsible for transporting the cumulus down the oviduct to the ampullar-isthmic junction (14). However, recent experiments by Halbert et al (5,6) have shown that pharmacological inhibition of smooth muscle contractility does not impair cumulus transport in the ampulla, which suggests that smooth muscle contractility may not be the primary propulsive force in this region of the oviduct. The effects of muscle activity alone on ovum transport in the ampulla have not been determined because of the unavailability of a method specifically to inhibit cilia activity.…”
mentioning
confidence: 97%
“…In the absence of muscular contractility following administration of isoproterenol in the rat oviductal ampulla, tubal transport of surrogate ova and their accompanying COC was unaffected implying that the cilia alone are adequate for transporting the ovum [55].…”
Section: Role Of Cbf In Gamete and Embryo Transportmentioning
confidence: 94%
“…Review of the literature showed that the isthmic portion demonstrated very high motility throughout the entire estrous cycle, whereas the ampulla presented an active pattern only during the periovulatory period (17). In addition, muscle contractions are the major driving force in the isthmus, whereas ciliary activity was the main power in the ampulla for the movement of the fertilized egg (18). Therefore, the isthmic segment of the fallopian tube at the estrus stage were chosen for study of smooth muscle contraction.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle contractions are the major driving force in the isthmus, whereas ciliary activity of the ampulla is the main power for the propelling the fertilized egg toward the uterine cavity (18). Pacemaker cells, named t-ICC, were found to exist in the myosalpinx, act as pacemakers and generate stabile cyclic electric signals to stimulate muscle contractions and make stirring movements in the oviduct (9,22).…”
Section: Control Mechanisms Of Oviduct Motilitymentioning
confidence: 99%